1997
DOI: 10.1103/physrevlett.79.3395
|View full text |Cite
|
Sign up to set email alerts
|

Surface Channeling Experiments at 20 MeV and Resonant Coherent Excitation ofN6+Ions

Abstract: Surface channeling of 21.8 and 23 MeV N 61 ions of a Pt(110) surface is experimentally verified. At 21.8 MeV resonant coherent excitation is observed leading to enhanced ionization when the ions scatter along the ͓110͔ surface half channels. [S0031-9007(97)04307-X] PACS numbers: 79.20.Rf, 34.50.Dy, 61.85. + p Channeling was first observed in a computer simulation [1]. The phenomenon was explained theoretically by a guided motion of the fast ions by the planar or cylindrical potentials formed by the planes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…If the velocity is high enough, this oscillating field could induce transitions between electronic states of the projectile. This, so-called, resonant coherent excitation or Okorokov process (Okorokov 1965, Datz et al 1978, Kupfer et al 1981, Kimura et al 1996, Kimura and Mannami 1998, Garcia de Abajo and Echenique 1996, Hatke et al 1997 has been observed for the 1s → 2p transition in atomic hydrogen grazingly scattered at an LiF(001) surface (Auth et al 1997. In the same way oscillating fields might lead to electron loss by transitions from the bound states to the continuum states above the vacuum level (Garcia de Abajo et al , 1994.…”
Section: Destruction Of Negative Ionsmentioning
confidence: 90%
“…If the velocity is high enough, this oscillating field could induce transitions between electronic states of the projectile. This, so-called, resonant coherent excitation or Okorokov process (Okorokov 1965, Datz et al 1978, Kupfer et al 1981, Kimura et al 1996, Kimura and Mannami 1998, Garcia de Abajo and Echenique 1996, Hatke et al 1997 has been observed for the 1s → 2p transition in atomic hydrogen grazingly scattered at an LiF(001) surface (Auth et al 1997. In the same way oscillating fields might lead to electron loss by transitions from the bound states to the continuum states above the vacuum level (Garcia de Abajo et al , 1994.…”
Section: Destruction Of Negative Ionsmentioning
confidence: 90%